Ikhtikar dan Dampaknya Terhadap Dunia Ekonomi - Muslim, Moch Bukhori (Al-Iqtishad: Journal of Islamic Economics, 2012)
There are some economic transactions that prohibited by religion because they only give benefit for one party. They are gambling, riba, fraudulence, al-ghabn, tadlis practice in buying and selling and hourding (ikhtikar). Therefore, it needs sense of transendence in every economical transaction. Ikhtikar is the economic activity undertaken by an economic agent with a hoard of goods in order to get maximum profit without seeing another person distress. In this case, the government should keep the market system which includes prohibiting ikhtikar, so the economic system can move with normal speed and full fairness. DOI: 10.15408/aiq.v4i1.2083